2008
DOI: 10.1038/mi.2008.14
|View full text |Cite
|
Sign up to set email alerts
|

Altered balance between Th17 and Th1 cells at mucosal sites predicts AIDS progression in simian immunodeficiency virus-infected macaques

Abstract: Loss of CD4 + T cells in the gut is necessary but not sufficient to cause AIDS in animal models, raising the possibility that a differential loss of CD4 + T-cell subtypes may be important. We found that CD4 + T cells that produce interleukin (IL)-17, a recently identified lineage of effector CD4 + T-helper cells, are infected by SIV mac251 in vitro and in vivo, and are found at lower frequency at mucosal and systemic sites within a few weeks from infection. In highly viremic animals, Th1 cells predominates ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
219
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(239 citation statements)
references
References 48 publications
17
219
2
1
Order By: Relevance
“…Th1 cells are the dominant subset in the gut mucosa during chronic infection, and the loss of Th1 cells in HIV/SIV infection impairs their responses to bacterial pathogens in gut mucosal tissues. 16,30 The decline of gut-homing Th1 cells during acute infection in our data (Figure 5b and 5c) indicates that a lack of Th1 cell recruitment from blood to the gut mucosa may occur during persistent HIV-1 infection and contribute to AIDS progression.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Th1 cells are the dominant subset in the gut mucosa during chronic infection, and the loss of Th1 cells in HIV/SIV infection impairs their responses to bacterial pathogens in gut mucosal tissues. 16,30 The decline of gut-homing Th1 cells during acute infection in our data (Figure 5b and 5c) indicates that a lack of Th1 cell recruitment from blood to the gut mucosa may occur during persistent HIV-1 infection and contribute to AIDS progression.…”
Section: Discussionmentioning
confidence: 77%
“…[15][16][17] Therefore, we determined the ratios of Th1:Treg, Treg:Th17, and Th1:Th17 of gut-homing CD4 1 T cells in AHIs. Acute HIV-1 infection led to a loss of guthoming Th1:Treg compared to HCs (Figure 6b), and the Treg:Th17 ratio increased in the gut-homing CD4 1 T-cell subset with statistical significance (Figure 6c).…”
Section: Imbalance Of Gut-homing Th1:treg and Treg:th17 Ratios In Acumentioning
confidence: 99%
See 1 more Smart Citation
“…First and foremost, it is possible that a different "quality" of CD4 ϩ T-cell depletion in natural versus nonnatural SIV hosts at the intestinal mucosal level plays a major role. Indeed, both SIV-infected RM and HIV-infected persons experience a significant and preferential reduction of the IL-17-producing CD4 ϩ (Th17) and CD8 ϩ (Tc17) T-cell subsets throughout the gastrointestinal tract (81)(82)(83)(84). Similarly, the depletion of IL-17-producing innate lymphocytes in the GI tracts of SIV-infected Asian macaques has been demonstrated (85,86).…”
Section: Pathogenesis Of Hiv/siv-associated Microbial Translocationmentioning
confidence: 94%
“…In a longitudinal study aimed at assessing the composition of microbial products translocating in peripheral blood prior to and during ART, we reported that patients with a poor immunological response to therapy exhibited a translocating bacterial microflora enriched in Enterobacteriaceae, with no evidence of probiotic Lactobacillus spp. (40), which are known to possess immunomodulatory and anti-inflammatory properties (106), including the suppression of proinflammatory cytokine production from E. coli LPS-activated monocytes (83). This change in the composition of the gut microbiome might result in a disproportionate antigenic challenge that is not contained by counterregulatory bacterially derived factors, overall exacerbating immune activation in this population of HIV-infected individuals.…”
Section: Characterization Of Stool Microbes and Translocating Flora Imentioning
confidence: 99%